PEMBANGUNAN WEBSITE KANTOR BMKG NGURAH RAI - Ni Putu Diva Damayanthi; Ida Ayu Gde Suwiprabayanti Putra; Putu Praba Santika (Jurnal Pengabdian Informatika, 2026)
The development of the Ngurah Rai BMKG Office website aims to enhance weather, climatology, and geophysical information services for the public, particularly in the I Gusti Ngurah Rai Airport area. This initiative includes designing and implementing key features such as a homepage displaying real-time weather information (METAR), early warnings, weekly weather forecasts, and satellite data. The methods applied encompass needs analysis, web-based system design, and implementation with role-based access control. The website effectively provides accessible information, with news, bulletins, and aviation documents managed through an admin login system. A notable achievement is the integration of real-time weather data to support airport flight operations. This development improves the efficiency of weather information dissemination and reinforces BMKG Ngurah Rai's digital services. The website is anticipated to significantly contribute to disaster mitigation efforts, aviation safety, and public needs.